Comparison of Accelerated Resolution Therapy (ART) for Treatment of Symptoms of PTSD and Sexual Trauma Between Civilian and Military Adults. Issue 9 (1st September 2015) - Kip, Kevin E.; Hernandez, Diego F.; Shuman, Amy; Witt, Ann; Diamond, David M.; Davis, Sheryl; Kip, Ryan; Abhayakumar, Alisha; Wittenberg, Trudy; Girling, Sue Ann; Witt, Steve; Rosenzweig, Laney
ABSTRACT: Objective: First-line psychotherapies for post-traumatic stress disorder (PTSD) were principally validated in civilian populations. We compared treatment of symptoms of psychological trauma between civilian and military adults by use of Accelerated Resolution Therapy (ART), an emerging, brief exposure-based therapy. Methods: We pooled individual patient data from two recently completed studies of ART. Treatment response for symptoms of PTSD was compared by civilian versus military status, stratified by gender and history of sexual trauma. Results: Mean age was 40.7 years in civilians ( n = 62) vs. 42.2 years in military participants ( n = 51). Mean PCL (PTSD) scores before/after treatment with ART were 53.2/30.2 among civilians compared with 56.0/40.5 among military participants (adjusted p = 0.25). Over follow-up ( n = 91), there was an apparent greater reduction among civilians in Intrusive ( p = 0.03) and Numbing symptoms ( p = 0.01), but not in Arousal ( p = 0.99) or Avoidance ( p = 0.19) symptoms. Among females with sexual trauma, mean reductions on the PCL were substantial in civilian (−22.5 ± 16.7) and military (−21.2 ± 12.7) participants ( p = 0.87). Conclusions: In an average of <4 treatment sessions, treatment with ART results in meaningful reductions in symptoms of PTSD in civilian and military patients. The suggestion of stronger response among civilians may owe to differential clinical presentation and trauma exposure history among military personnel.